2018
DOI: 10.1182/blood-2018-01-828277
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-intensity conditioning for hematopoietic cell transplant for HLH and primary immune deficiencies

Abstract: Allogeneic hematopoietic cell transplantation (HCT) with myeloablative conditioning for disorders associated with excessive inflammation such as hemophagocytic lymphohistiocytosis (HLH) is associated with early mortality. A multicenter prospective phase 2 trial of reduced-intensity conditioning with melphalan, fludarabine, and intermediate-timing alemtuzumab was conducted for HLA matched or single HLA locus mismatched related or unrelated donor HCT in a largely pediatric cohort. Graft-versus-host disease (GVHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 39 publications
3
73
2
Order By: Relevance
“…The relatively uniform achievement of high myeloid chimerism early post-BMT is notable, and we postulate this to be related to a potent and early graft-versusmarrow effect, as the preparative regimen was not myeloablative. The use of DLI was not infrequent in this study, as similarly reported with other RIC-BMT approaches and best captured in a multicenter, phase II trial of RIC-BMT for PID by Allen and colleagues [27] in which 50% of patients had graft failure or required DLI for falling/low donor chimerism and the 1-year probability of being alive with sustained engraftment (>5% donor cells in whole blood) without intervention was 39%, with 61% alive with sustained engraftment with or without intervention. Using the same engraftment definitions, our platform compares favorably, with 1-year probability of survival with sustained engraftment without intervention of 75% and with or without intervention of 85%; most patients became full-donor chimeras without intervention, often following the cessation of GVHD prophylaxis with sirolimus.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The relatively uniform achievement of high myeloid chimerism early post-BMT is notable, and we postulate this to be related to a potent and early graft-versusmarrow effect, as the preparative regimen was not myeloablative. The use of DLI was not infrequent in this study, as similarly reported with other RIC-BMT approaches and best captured in a multicenter, phase II trial of RIC-BMT for PID by Allen and colleagues [27] in which 50% of patients had graft failure or required DLI for falling/low donor chimerism and the 1-year probability of being alive with sustained engraftment (>5% donor cells in whole blood) without intervention was 39%, with 61% alive with sustained engraftment with or without intervention. Using the same engraftment definitions, our platform compares favorably, with 1-year probability of survival with sustained engraftment without intervention of 75% and with or without intervention of 85%; most patients became full-donor chimeras without intervention, often following the cessation of GVHD prophylaxis with sirolimus.…”
Section: Discussionsupporting
confidence: 76%
“…Using the same engraftment definitions, our platform compares favorably, with 1-year probability of survival with sustained engraftment without intervention of 75% and with or without intervention of 85%; most patients became full-donor chimeras without intervention, often following the cessation of GVHD prophylaxis with sirolimus. The ability of unconditioned DLI to improve mixed chimerism after BMT may ultimately be low, but data presented here and by others suggest that mixed chimerism may not require intervention with DLI, given that it can be stable over time and sufficient for phenotype reversal for some PIDs [23,24,27,32]. Although PTCy is known to decrease chronic GVHD incidence effectively, including in PID patients [23,25,[33][34][35], the complete absence of chronic GVHD in this study, confirmed on serial, comprehensive evaluations, is one of the most clinically important and promising findings.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…As with other alemtuzumab‐based RIC approaches, sustained engraftment was poor with fewer than half (41% of patients with HLH) being engrafted without secondary graft failure, need for donor lymphocyte infusion (DLI) or second transplant and alive at one year. Although the survival outcomes compared favourably to MAC regimens, long‐term durable engraftment was suboptimal (Allen et al , ).…”
Section: Patient Characteristics and Outcomementioning
confidence: 99%
“…We report our results incorporating thiotepa into the fludarabine/melphalan/alemtuzumab (day‐14) backbone (Marsh et al , ; Allen et al , ). In recent reports, the addition of thiotepa during conditioning was shown to be safe and was associated with enhanced engraftment across a range of donor sources (Ciurea et al , ; Larsen et al , ).…”
Section: Patient Characteristics and Outcomementioning
confidence: 99%